2004
DOI: 10.1089/1536859041651295
|View full text |Cite
|
Sign up to set email alerts
|

Phage Display Selection of scFv to Murine Endothelial Cell Membranes

Abstract: The diversity of endothelial cells is becoming more apparent and more important in defining vessel systems that supply blood to normal organs and to tumors. Reagents that identify expression of cell surface determinants on these cells are crucial for differentiating among different vessel types. As a first step in this process we have selected a panel of 25 scFvs from a phage display library that bind to the endothelial cell line LEII. The scFvs are of high affinity and bind to some tumor cells as well as to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Soluble scFv fragments protein expression levels for these clones were in the range of 0.044 to 1.8 mg/liter of culture. These yields are in general agreement with published yields in the range of 0.1 to 5.0 mg per liter of E. coli culture for clones isolated from the Tomlinson libraries (Kennel et al, 2004; Wu et al, 2007; Lobova et al, 2008). SDS-PAGE analysis for these four clones show bands corresponding approximately to 26–28 kD molecular weight when compared to the 25 kD band of the protein standard ladder run in parallel with the samples (Fig.…”
Section: Resultssupporting
confidence: 89%
“…Soluble scFv fragments protein expression levels for these clones were in the range of 0.044 to 1.8 mg/liter of culture. These yields are in general agreement with published yields in the range of 0.1 to 5.0 mg per liter of E. coli culture for clones isolated from the Tomlinson libraries (Kennel et al, 2004; Wu et al, 2007; Lobova et al, 2008). SDS-PAGE analysis for these four clones show bands corresponding approximately to 26–28 kD molecular weight when compared to the 25 kD band of the protein standard ladder run in parallel with the samples (Fig.…”
Section: Resultssupporting
confidence: 89%
“…This method uses repetitive cycles of intravenous injections of phages encoding stochastic peptides, which may bind to sites accessible to the circulation, followed by the identification of specific phages homing into selected tissues and the eventual isolation of the homing determinants [151]. This method becomes more popular in the analysis of specific endothelial surface determinants, especially those characteristic of pathologically altered endothelium in tumours and atherosclerotic lesions, both in cell cultures and in vivo [55,[152][153][154][155][156][157]. Some of the affinity ligands defined by this methodology, including those binding to previously identified endothelial determinants including adhesion molecules and ectopeptidases, are currently being explored for vascular targeting of imaging probes and drugs in animals [158].…”
Section: Quest For Novel Determinants: Endothelial Genomics Proteomimentioning
confidence: 99%
“…Mice were sacrificed after 1 hour and biodistribution was determined. 8,24 Immunohistochemistry After deparaffinization, slides of 5-m-thick tumor sections were deparaffinized and treated for antigen retrieval with citrate buffer pH 6.0 (for vWF and CD34 staining) and pepsin (Biogenex; San Ramon, CA) digestion for laminin staining. Slides were blocked prior to the primary antibody incubation.…”
Section: Scfv Biodistributionmentioning
confidence: 99%
“…We have tested several libraries for the identification of specific scFvs. 24 The Tomlinson I and J scFv phage libraries were selected for this study, as they have a stable framework, have been preselected for properly folded scFv, and employ a trypsin-sensitive site as a specific means to elute selected phage from their target. In this study, we identified 17 antilaminin-1 scFvs, representing at least four epitope groups.…”
Section: Introductionmentioning
confidence: 99%